Novas estratégias de reprodução do capital em espaços comerciais de pequenas cidades paraibanas - Silva, Izabelle Trajano da (2021)
This study aimed to understand how new capital reproduction strategies materialize in commercial spaces in small towns in Paraíba and influence their socio-spatial dynamics. Six small towns in the state of Paraíba (Juazeirinho, Monteiro, Queimadas, Serra Branca, Soledade and Sumé), which form the intermediate geographic region of Campina Grande, were the objects that provided the developed analyses. The recognition of commercial forms, characterized as unprecedented (associative networks, franchise units and loyal stores), was the starting point of the trajectory of this research. But by recognizing that space is not produced only by content-forms, it was also investigated the consumption practices of residents in the spatial analysis. Thus, in relation to the data collection instruments, it was accomplished: application of questionnaires (with associative networks, franchise units and with residents of the cities studied), conducting interviews (with those responsible for the loyal stores) and photographic records (in addition to surveys on websites and digital social networks, such as Facebook and Instagram, from institutions that had them). The collected material generated a considerable database which, combined with the observation carried out during the fieldwork, allowed us to make considerations that went beyond a simple characterization of commercial forms. The questionnaires applied to the resident population also revealed a fourth new commercial form (e-commerce) which, in urban spaces, presents itself paradoxically unnoticed (due to its hidden spatial form) and imposing (as a driving force of consumption). It was found that new strategies for the reproduction of capital materialize in commercial spaces in small towns in Paraíba, printing new content-forms, which are characterized by the reproduction of stimuli to recurrent consumption and, for this, they use various merchandising practices (marketing actions) that seek the continuous return of consumers to the same establishments. Another characteristic observed was the realization of commerces that occur from the use of symbolic power exercised by the name (brand) that represents it. In this case, the formation of the consumer precedes the production of the merchandise. Finally, it is necessary to highlight the considerable attractiveness of local commerce for residents of the cities studied (given the high rate of purchases made by the survey participants in their respective towns) and the significant commercial plurality (existing in the landscapes and expressed by the residents participating in the research). It is understood that all changes on commerce and consumption, identified and described in the spatial analysis, deal with the context of the capitalist economy that, over time, created a greater need for demand so that merchandises could be produced and consumed and so that money (resulting from the sales of these merchandises) could return again to the movement of capital circulation. In this scenario, the technical-scientific-informational environment is the support of commercial innovations. Therefore, this thesis is an opportunity to not only know more about the realization of capitalist reproduction in its general aspects (there are already a multitude of works for this), but it is also an opportunity for the (re)cognition of the realization of this global phenomenon in a scale called small town (Paraiba).